A scoping review of integrated arts therapies and neuroscience research - Rebecca Bokoch; Noah Hass-Cohen; April Espinoza; Tyler O’Reilly; Elad Levi (Frontiers in Psychology)
IntroductionThis article provided a scoping review of the current state of the field for integrated arts therapies and neuroscience research. The main arts therapies modalities included in this review were: of arts therapies (i.e., drawing, painting, sculpting, bibliotherapy, cinema therapy, dance movement therapies, drama therapies, music therapies, neuroaesthetics, phototherapies, and poetry). The main objectives of this integrated arts therapies and neuroscience scoping review were to: (1) include multiple modalities of arts therapies, (2) summarize, synthesize, compare, and contrast populations, settings, presenting problems, methods, modalities, measures, and outcomes, (3) discuss implications, and (4) suggest future directions.MethodsThe design for this scoping review was conducted according to PRISMA-ScR and the JBI Scoping Review Manual standardized recommendations. Eligibility criteria included: English language, peer-review, integration of arts therapies and neuroscience, and use of research methodologies such as case studies, quantitative, qualitative, mixed methods, systematic or scoping reviews, and meta-analyses. Articles were gathered from two online databases (EBSCOHost and PubMed) using keywords, and review of articles from reference lists. Publications that met criteria were reviewed and charted for the following information: author, year of publication, sample size and characteristics, research design, data analyses, modality (i.e., intervention, treatment), and outcomes. This scoping review included 84 publications that met inclusion criteria, after the research team discussed to consensus.ResultsOutcomes suggested improvements in brain activity and integration, cognitive, affective, sensory, and social functioning, memory reconsolidation, psychological symptoms, affect, and behavior.DiscussionInterpretations were limited in that most publications lacked directionality in their approach, were exploratory, and dependent on researcher assumptions, expertise, and access to instruments and populations. Therefore, more research is needed on each modality that upholds stronger research methodology, and can develop focus across researchers. While this scoping review was able to summarize and synthesize the state of the field, it is still too early to be able to compare outcomes or make more solid conclusions about specific neuroscientific processes and benefits for each individual modality. This body of knowledge provided valuable implications for the field and made suggestions for future directions.